Current Academic Clinical Trials in Ovarian Cancer: Gynecologic Cancer Intergroup and US National Cancer Institute Clinical Trials Planning Meeting, May 2009. Issue 7 (1st October 2010) - Trimble, Edward L.; Birrer, Michael J.; Hoskins, William J.; Marth, Christian; Petryshyn, Ray; Quinn, Michael; Thomas, Gillian M.; Kitchener, Henry C.; ,
Abstract : Objective: To review the current status of large phase academic clinical trials for women with ovarian cancer, address cross-cutting issues, and identify promising areas for future collaboration. Methods: In May 2009, the Gynecologic Cancer Intergroup, which represents 19 Cooperative Groups conducting trials for women with gynecologic cancer, and the US National Cancer Institute convened a Clinical Trials Planning Meeting. Results: The topics covered included the impact of new developments in cancer biology upon molecular targets and novel agents, pharmacogenomics, advances in imaging, the potential benefit of diet and exercise to reduce the risk of recurrence, academic partnership with industry, statistical considerations for phases 2 and 3 trials, trial end points, and symptom benefit and health-related quality-of-life issues. The clinical trials discussed spanned the spectrum of ovarian cancer from initial diagnosis, staging, and cytoreductive surgery to consolidation chemotherapy, and treatment of recurrent disease. Conclusions: Ongoing and effective collaboration with industry, government, and patients aims to ensure that the most important scientific questions can be answered rapidly. We encourage women with ovarian cancer and their oncologists to consider participation in the academic clinical trials conducted by the member groups of the Gynecologic Cancer Intergroup.